A New Deal for the Arts - USA - National Archives and Records Service (2006)
[Dt.:] Die online-Ausstellung "A New Deal for the Arts", widmet sich der Kunstförderung während des New Deals in den USA anhand exemplarischer Künstlerpositionen. Thumbnails sind vergrößerbar. Die Präsentation rekurriert auf die gleichnamige Ausstellung im National Archives (Washington, DC) 1998. - [Engl.:] The New Deal arts projects provided work for jobless artists, but they also had a larger mission: to promote American art and culture. The exhibition describes and displays the work of the New Deal arts projects and discusses themes common to this government-sponsored art. The online exhibit is adapted from "A New Deal for the Arts," an exhibit that was on display in 1998, in the National Archives (Washington, DC). Thumbnails can be zoomed.